A High Efficiency Si Photoanode Protected by Few‐Layer MoSe2. Issue 8 (6th June 2018) - Vanka, Srinivas; Wang, Yongjie; Ghamari, Pegah; Chu, Sheng; Pandey, Ayush; Bhattacharya, Pallab; Shih, Ishiang; Mi, Zetian
Abstract : To date, the performance of semiconductor photoanodes has been severely limited by oxidation and photo‐corrosion. Here, a report is given on the use of earth‐abundant MoSe2 as a surface protection layer for Si‐based photoanodes. Large area MoSe2 film was grown on p + ‐n Si substrate by molecular beam epitaxy. It is observed that the incorporation of few‐layer (≈3 nm) epitaxial MoSe2 can significantly enhance the performance and stability of Si photoanode. The resulting MoSe2 / p + ‐n Si photoanode produces a light‐limited current density of 30 mA cm −2 in 1 M HBr under AM 1.5G one sun illumination, with a current‐onset potential of 0.3 V versus reversible hydrogen electrode (RHE). The applied bias photon‐to‐current efficiency (ABPE) reaches up to 13.8%, compared to the negligible ABPE values (<0.1%) for a bare Si photoanode under otherwise identical experimental conditions. The photoanode further produced stable voltage of ≈0.38 V versus RHE at a photocurrent density of ≈2 mA cm −2 for ≈14 h under AM 1.5G one sun illumination. This work shows the extraordinary potential of two‐dimensional transitional metal dichalcogenides in photoelectrochemical application and will contribute to the development of low cost, high efficiency, and highly stable Si‐based photoelectrodes for solar hydrogen production. Abstract : The incorporation of few‐layer (≈3 nm) epitaxial MoSe2 can significantly enhance the performance and stability of Si photoanode. The resulting MoSe2 / p + ‐ n Si photoanode produces a light‐limited current density of 30 mA cm −2 in 1M HBr under AM 1.5G one sun illumination, with a current‐onset potential of 0.3 V versus reversible hydrogen electrode (RHE). The applied bias photon‐to‐current efficiency reaches 13.8% at 0.5 V versus RHE.